Síntese e avaliação do potencial de uma meso-porfirina, derivada do LCC, como desativadora dos metais pesados: cádmio, chumbo e níquel - Girão, Fátima Andréa Lima (2008)
The search for chemical processes that reduce or eliminate the use and generation of hazardous substances has been growing in recent decades. With this new direction for reducing the impact of industrial activities, were alternative proposals that can reduce the environmental impact. In this respect, we were synthesized meso-porfirnas A4 type (meso-5,10,15,20) from the Net peel Cashew nuts - LCC (a renewable source, location, abundant and biodegradable). The meso-porphyrin used in this work was obtained from CNSL distillation process. The first derivative refers to the formation of the brominated compound, followed by obtaining the aldehyde derivative finally with the aid of pyrrole, is the formation of meso-porphyrin. The compounds were purified by column chromatography and characterized by experimental techniques 13C and 1H NMR, GC-MS, IR and UV-VIS, which confirmed to obtain the desired product. The free base porphyrin metallation was subjected to procedures for using it, Ni (C2H3O2) .4H2O, Cd (CH3COO) 2 and Pb (CH3COO) 2 as the metal salt and donor dichloromethane as solvent, the reaction according to the methodology remained constant stirring. The metallation was followed by UV-VIS spectroscopy and thin layer chromatography